64.7k views
3 votes
Y= 3/5x -5 and x+3y=-1 how do i solve this using elimination

1 Answer

3 votes

Answer:

x = 5 and y = -2

Explanation:

Two equations are given and we have to solve those two equations by elimination process.

The equations are


y = (3)/(5) x - 5

⇒ 5y = 3x - 25

3x - 5y = 25 ......... (1) and

x + 3y = - 1

⇒ 3x + 9y = -3 ........... (2)

Now, eliminate x from equations (1) and (2) by {(2) - (1)}

14y = - 28

y = - 2

Now, from equation (1) we get, 3x = 25 + 5y = 15

x = 5

Therefore, the solution of the given equations are x = 5 and y = -2. (Answer)

User Ansara
by
5.6k points